PERMASALAHAN STUNTING PADA IBU HAMIL DAN BALITA DI DESA ROWOREJO LAMPUNG BARAT - Furqon, Ahmad Fauzi (Universitas Khairun, 2024)
Stunting is a health problem that is a priority for creating quality Indonesian human resources. The key to successful stunting prevention is nutritional monitoring and weight measurement of babies and toddlers carried out by community cadres at posyandu. This research is a purely descriptive study, which took place in a village that is a stunting locus, namely Roworejo Village. Data collection time was carried out in July. Data collection was carried out first, collecting information regarding the level of stunting in Roworejo village. To achieve the goal, the KKN 468 group took a direct approach to the health team and the Roworejo village community. The results of the research are for the public to increase their knowledge about stunting and the importance of maintaining the nutritional quality of food.